Kekuatan Tarik dan Porositas Hasil Sambungan Las Gesek Aluminium 6061 dengan Berbagai Suhu Aging - Setyawan, Pungky Eka; Irawan, Yudy Surya; Suprapto, Wahyono (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2014)
Aluminum alloy is one of materials that is difficult joining with fusion welding. Friction welding is solution to solve engineering problems in joinning with fusion welding. The parametersthat influence onfriction weldingare frictiontime, rotational speed, compressive force, and upset force. In this study, specimens were friction welded with rotation speed of 1600 rpm, compressive force during friction welding 123 kgf for 120 seconds, and upset force 202 kgf for 120 seconds.The weakness of the friction welding process is a decline in strength, it is due to friction welding is done in solid condition. In order to increase tensile strength of friction welding joint, precipitation hardening methods can be used.Precipitation hardening methods carried out in three stages, solution heat treatment, quenching and agingwith artificial aging process. The artificial aging temperature variated by 150 C, 185 0 C 200 0 C, and 225 0 C with a holding time in 7 hours. The results showed that precipitation hardening cause porosity decreasedin the weld joint. Specimens with a aging temperature 150 0 C and holding time for 7 hours has the smallest porosity of 0,11 % and it has maximum tensile strength of 186,65 MPa.Keywords: Tensile Strength, Pososity, Friction Welding, Aging Treatment.